2003
DOI: 10.1034/j.1600-6143.2003.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant MELD Score As a Predictor of Outcome After Liver Transplantation for Chronic Hepatitis C

Abstract: The Model of End-Stage Liver Disease (MELD) score, an accurate predictor of mortality in patients awaiting liver transplantation (OLTX), did not predict graft or patient survival in the post-transplant setting. Our aim was to test the model in patients who underwent OLTX for chronic hepatitis C. Two hundred and eighty-seven adult patients who underwent primary OLTX for chronic hepatitis C between December 1993 and September 1999 were studied from a prospectively maintained database. The group was stratified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
2
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 19 publications
(13 reference statements)
0
42
2
1
Order By: Relevance
“…In a single center study, Saab et al (9) showed that patients with pretransplant MELD scores above 36 had a hazard ratio of 3.9 for posttransplant death compared to patients with MELD scores 36 and below. In a separate single center experience, Onaca et al (10,11) showed a statistical difference in a 2-year survival after transplant in patients with pretransplant MELD scores above 25. This difference was only shown to be significant in patients with hepatitis C and noncholestatic liver diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a single center study, Saab et al (9) showed that patients with pretransplant MELD scores above 36 had a hazard ratio of 3.9 for posttransplant death compared to patients with MELD scores 36 and below. In a separate single center experience, Onaca et al (10,11) showed a statistical difference in a 2-year survival after transplant in patients with pretransplant MELD scores above 25. This difference was only shown to be significant in patients with hepatitis C and noncholestatic liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The performance of the MELD score in predicting posttransplant survival has been more variable (9)(10)(11)(12)(13) but it is generally accepted that patients with very high MELD scores prior to transplant have worse outcomes than those with lower MELDs. With discussion of incorporation of the delta-MELD into organ allocation systems, the question of whether patients with high pretransplant delta-MELD scores have worse posttransplant outcomes would be critical in determining if this change in allocation system would increase posttransplant death rates.…”
Section: Introductionmentioning
confidence: 99%
“…The post-LT mortality was high in our cohort. Significant predictors of post-LT mortality included previously reported factors among the overall recipient population, and donor factors (older donor, prolonged cold ischemia time, and cause of donor death other than head trauma, stroke, or anoxia) (26)(27)(28)(29). These three donor factors are components of the donor risk index (29).…”
Section: Discussionmentioning
confidence: 99%
“…15 In contrast to the clear benefit of accurately estimating mortality on the waiting list, MELD has not been found to be as useful in predicting mortality following liver transplantation. [16][17][18][19] Mortality in the post transplantation period is related not only to the degree of liver dysfunction prior to transplantation, but to other factors, such as donor characteristics, experience of the transplantation team, and random postoperative complications which cannot be predicted. Moreover, patient selection by physicians will tend to negate the effect of pre-transplant MELD on post transplant survival.…”
Section: Meld In Liver Transplantationmentioning
confidence: 99%